1999
DOI: 10.1136/jnnp.67.5.613
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for spread of primary adult onset blepharospasm: a multicentre investigation of the Italian movement disorders study group

Abstract: Objectives-Little is known about factors influencing the spread of blepharospasm to other body parts. An investigation was carried out to deterrmine whether demographic features (sex, age at blepharospasm onset), putative risk, or protective factors for blepharospasm (family history of dystonia or tremor, previous head or face trauma with loss of consciousness, ocular diseases, and cigarette smoking), age related diseases (diabetes, hypertension), edentulousness, and neck or trunk trauma preceding the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
3
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 21 publications
(25 reference statements)
5
45
3
7
Order By: Relevance
“…Defazio et al [11] also did not find a significant association between spread of primary adult-onset blepharospasm and family history of dystonia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Defazio et al [11] also did not find a significant association between spread of primary adult-onset blepharospasm and family history of dystonia.…”
Section: Discussionmentioning
confidence: 92%
“…Descendent spread lead to development of segmental dystonia in a third of our patients. Deffazio et al [11] reported further spread of dystonia in 35% of cases with blepharospasm. Green et al [4] found two times higher estimate of further dystonia spread in patients with blepharospasm (70%), also affecting respiratory muscles in 10%.…”
Section: Discussionmentioning
confidence: 97%
“…This finding and the lack of correlation between age at menopause and age at BSP onset indicate that menopause probably exerts no significant influence on the age-dependent development of BSP. Likewise, it was previously shown that menopause did not affect the spread of dystonia to neighboring muscles in patients with BSP-onset cranial cervical dystonia [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Описаны редкие случаи поражения других мышц через 10 лет и более после начала заболевания [29][30][31][32].…”
Section: Cranial Dystonia Is a Common Disease Of The Extrapyramidal Nunclassified
“…Defazio и соавт. [29], обследовав 155 пациентов с блефароспазмом, выявили следующие предикторы даль-нейшего распространения заболевания: наличие в анамнезе черепно-мозговой травмы с нарушением сознания, возраст возникновения блефароспазма и женский пол. В другом ис-следовании значительных различий между мужчинами и женщинами в вероятности распространения дистоническо-го гиперкинеза не отмечено [28].…”
Section: неврология нейропсихиатрия психосоматика 2018;10(1):90-95unclassified